High prevalence of parental delivery of plastic debris in Cory’s shearwaters (Calonectris diomedea) - Rodríguez, Airam; Rodríguez, Beneharo; Carrasco, María Nazaret (Marine Pollution Bulletin, 2012)
Plastic ingestion by adult Procellariiformes has been widely recorded, but few studies have evaluated intergenerational transfer. We assessed the prevalence of plastic particles, as well as their basic character- istics, in the gut content of dead Cory’s shearwater ﬂedglings stranded by light pollution on Canary Islands. Eighty-three percent of birds were affected, containing on average 8.0 plastic pieces per bird. The average plastic weight per bird was low (2.97 ± 3.97 mg) compared with other petrel species. We found no rela- tionships between plastic loads and body condition or body size, but negative effects may be hidden or delayed. We propose to use the ﬂedglings stranded by light pollution to carry out more precise studies to understand the potential hidden costs of plastic ingestion; and to monitor in a long-term the marine debris to develop management actions for the control of pollution at the marine environment Peer reviewed